Place of origin associated with depressive symptoms in health professionals performing social health service in Ancash, Peru, 2015 - Maticorena-Quevedo, Jesus (2018)
Introduction: Health professionals performing their social health service (SHS) in rural communities could be at risk of developing depression. Moreover, those who migrate from farther places to perform their SHS could have an increased risk. The objective of this study was to evaluate the association between place of origin and the presence of depressive symptoms, in health professionals performing rural social health service (SHS) in Ancash, Peru. Methods: This was a cross-sectional study. During April 2015, a survey was applied to health professionals performing SHS in the Peruvian Ministry of Health (MINSA) facilities in Ancash. The main outcome was the presence of depressive symptoms, defined as a score ≥2 points in the Patient Health Questionnaire-2. The main exposure was the place of origin, defined as the place where the subjects completed their undergraduate professional studies (Ancash, Lima city or others). Poisson regressions with robust variance were performed to calculate crude and adjusted prevalence ratios (PR and aPR) and their 95% confidence interval (95%CI). Results: From 573 health professionals performing their SHS in MINSA in Ancash, 347 were included in the study. The mean age was 27.2±4.5 years, 78.7% were women, and 14.7% scored positive for depressive symptoms. Those who had completed their undergraduate professional studies in Lima city had a higher prevalence of presence of depressive symptoms compared to those who did in Ancash (aPR=2.59, 95%CI=1.23–5.45). Conclusions: Those who completed their undergraduate professional studies in Lima had a higher prevalence of depressive symptoms than those who did in Ancash. Possible explanations include the difficulty in visiting family and friends, acculturation, and lack of Quechua language proficiency.